PERAN GURU AGAMA DALAM BIMBINGAN KONSELING SISWA SEKOLAH DASAR - Ridwan, Amin (Risâlah, Jurnal Pendidikan dan Studi Islam, 2018)
Karakteristik siswa sekolah dasar sanga tunik. Perilaku dan model komunikasinya sanga tunik karena bawaan sifat kekanak-kanakannya. Guru Sekolah Dasar (SD) yang terdiri dari guru kelas, guru matapelajaran, merupakan ujung tombak pelaksanaan pendidikan di sekolah dasar. Demi terselenggarannya kegiatan bimbingan di SD, sangat diperlukan peran serta kepala sekolah dan guru Agama serta personil lain yang ada di SD. Jurnal ini membahas definisi peserta didik sekolah dasar serta model bimbingan dan konselingnya. Learners in primary schools have very distinctive characteristics to the nature of childhood, ranging from models of Conduct to communicate. Business in primary school usually consists of principals, classroom teachers, subject teachers, operator up to the administrative staff are the spearhead of the implementation of education and teaching. Indeed, teacher guidance and counseling specifically yet. But the implementation of all personnel in primary schools in a comprehensive manner. For the sake of implementation guidance activities in primary schools, indispensable role of the school principal, it is very necessary role of principals and teachers of religion and other personnel in elementary school. This journal discusses the definition of primary school learners as well as guidance and counseling models.